Meningkatkan Kualitas Ibadah Shalat Siswa Melalui Pembelajaran Shalat dengan Metode Praktek Langsung dI SMAN 1 Muko Muko - Fitriani; Endang elfitra (GHAITSA : Islamic Education Journal, 2025)
This study aims to improve the quality of students' prayer through the application of direct practice method in learning at SMAN 1 Muko Muko. The low quality of prayer worship, both in the aspects of reading, movement, and solemnity, is one of the main challenges in Islamic religious education. The traditional approach that focuses on theory has not been effective in improving students' understanding and practice of prayer. Therefore, this study adopts a hands-on practice-based learning method, which allows students to practice prayer directly with the guidance of the teacher. This method is expected to improve technical aspects, solemnity, and consistent prayer habits. This research design utilizes the classroom action research (PTK) method with a descriptive qualitative approach. The results showed a significant improvement in the quality of students' prayers. Before the application of this method, only about 40% of students performed the prayer correctly, while after three learning cycles, the percentage increased to 75%. In addition, students' solemnity also improved, with 65% of students showing significant improvement. The findings indicate that the hands-on method not only improves students' technical skills, but also deepens their understanding and spiritual awareness in performing acts of worship. This research suggests a wider application of the direct practice method in learning prayer in schools, as well as the importance of a comprehensive evaluation of the technical and affective aspects of the implementation of prayer. It is hoped that the results of this study can be a reference for the development of a more effective and applicable Islamic Religious Education curriculum, and contribute to the formation of noble student characters.